1981
DOI: 10.1093/infdis/143.6.791
|View full text |Cite
|
Sign up to set email alerts
|

A 27-nm Virus Isolated During an Outbreak of Acute Infectious Nonbacterial Gastroenteritls in a Convalescent Hospital: A Possible New Serotype

Abstract: An outbreak of acute infectious nonbacterial gastroenteritis began among elderly patients in a convalescent hospital in Marin County in northern California in March 1978 and persisted through May 1978. The overall clinical attack rate was 51% of 187 residents and 12% of 180 employees. A 27-nm viruslike particle was observed by immune electron microscopy in stools obtained at or near the onset of illness from four of 32 patients. Seroresponses to the 27-nm particles were found by immune electron microscopy in 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

1983
1983
2010
2010

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 16 publications
1
41
0
Order By: Relevance
“…Children, from infancy to 5 to 7 years of age, are most likely to develop symptomatic disease with astroviruses (7,204,210), although exposed adults can also develop mild disease, but with less frequency (204,210,278). In one study (210), older children were also found to be less likely to develop disease than younger children.…”
Section: Astrovirusesmentioning
confidence: 98%
See 2 more Smart Citations
“…Children, from infancy to 5 to 7 years of age, are most likely to develop symptomatic disease with astroviruses (7,204,210), although exposed adults can also develop mild disease, but with less frequency (204,210,278). In one study (210), older children were also found to be less likely to develop disease than younger children.…”
Section: Astrovirusesmentioning
confidence: 98%
“…They are responsible for about 5% of infantile gastroenteritis, including nosocomial infections. The Marin County agent, discovered in elderly patients with diarrhea in a convalescent hospital in California, is also an astrovirus (148,278). Their appearance has been described in detail by Madeley (227).…”
Section: Astrovirusesmentioning
confidence: 99%
See 1 more Smart Citation
“…Norwalk virus was the first of these viruses to be characterized and serves as the epidemiologic prototype for the group. Norwalk-like viruses are small, round, morphologically similar viruses 25 to 30 nm in diameter (3,12,67,93). Individual viruses (Norwalk, Hawaii, Snow Mountain, and Otofuke viruses) have been named for the locations of outbreaks from which the virus was first isolated.…”
Section: Agents Of Viral Gastroenteritis Associated With Outbreaks Ofmentioning
confidence: 99%
“…However, no other food was prepared by him and it is most likely that the sandwiches were the passive vehicle that spread the virus. Oshiro et al (1981) described an outbreak of acute non-bacterial gastroenteritis among the elderly patients in a convalescent home in North California which persisted for 14 months. The responsible agent was shown to be serologically unrelated to the Norwalk virus.…”
Section: Discussionmentioning
confidence: 99%